Subsemi-Eulerian graphs - Charles Suffel; Ralph Tindell; Cynthia Hoffman; Manachem Mandell (International Journal of Mathematics and Mathematical Sciences)
A graph is subeulerian if it is spanned by an eulerian supergraph. Boesch, Suffel and Tindell have characterized the class of subeulerian graphs and determined the minimum number of additional lines required to make a subeulerian graph eulerian.